Adalimumab: A key element in the treatment strategy for immune-mediated inflammatory diseases: A review - Mariam A. Gilavian; Daria V. Trunova; Anastasia V. Ustinova; Anna M. Sukhanova (ZAO "Consilium Medicum", 2024)
Adalimumab is a biological drug effectively used in the treatment of several immune-mediated inflammatory diseases, including ankylosing spondylitis, juvenile idiopathic arthritis, and psoriasis. This study analyzed the therapeutic and economic benefits of adalimumab. Patients with ankylosing spondylitis showed significant improvements in quality of life and work productivity after treatment with adalimumab, confirming its clinical and economic efficacy. In the case of juvenile idiopathic arthritis and psoriasis, adalimumab demonstrated high efficacy and safety, significantly improving patients' conditions, establishing it as the gold standard of therapy. The use of adalimumab biosimilars offers accessible alternatives to the original drugs, expanding treatment options and reducing the economic burden on patients.